The impact of training chemotherapy safety standards with a smartphone application on the knowledge, attitude, and performance of nurses - Zohreh Hojati; Fateme Goudarzi; Shirin Hasanvand; Nasrin Galehdar; Mehdi Birjandi (BMC, 2023)
Abstract Background Nurses who play the leading role in caring for patients, especially nurses in the chemotherapy department who are constantly exposed to high-risk drugs and their side effects, should pay more attention to occupational safety. This study was performed to determine the effect of training chemotherapy safety standards using a smartphone application on nurses' knowledge, attitude, and performance. Methods The whole enumeration of fifty oncology nurses was recruited who they worked in 3 hospitals affiliated with Lorestan University of Medical Sciences (west of Iran). The study was conducted from June to November 2021. The training was done for four weeks with a smartphone application, including six main courses of familiarity with hazardous drugs, Personal Protective Equipment, preparation, storage and transfer, spilling, and wastes disposal of hazardous drudges . The nurses' knowledge, attitude, and performance questionnaire were completed before, immediately after, and one month after the intervention. Data analysis was performed using SPSS version 26, descriptive and inferential statistical tests of independent t-test, one-way analysis of variance, Spearman's rank correlation coefficient, repeated measures analysis of variance, and the Generalized Estimating Equation (GEE) model. Results Mean knowledge score of participants before, immediately after, and one month after the intervention was (47.18 ± 8.19), (60.08 ± 3.82), and (61.88 ± 3.45), respectively. The mean attitude score of participants before, immediately after, and one month after the intervention was (30.34 ± 3.94), (34.32 ± 3.25), and (34.98 ± 2.88), in order, and the mean performance score of participants before, immediately after, and one month after the intervention was (43.60 ± 5.11), (51.78 ± 3.15) and (52.88 ± 3.06), respectively. The mean nurses' knowledge, attitude, and performance score increased significantly over time (P < 0.001). Conclusions Teaching chemotherapy safety standards using the application improved oncology nurses' knowledge, attitude, and performance. Appropriate educational programs, especially by new methods such as E-learning, are recommended for providing safety for nurses.